Pengaruh Latar Belakang Agama dan Nilai Akademik terhadap Pemahaman Mata Kuliah Akuntansi Syariah (Studi Empiris pada Mahasiswa Akuntansi di Universitas Jember) - Ike Aprilia Trisdianti; Moch. Shulthoni; Eza Gusti Anugerah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This research was conducted on undergraduate accounting students class of 2020 and 2021 at the University of Jember. The purpose of this study was to determine the effect of understanding Sharia Accounting courses with Religious Background and Academic Grades. The data instrument used is using a questionnaire with the slovin formula on 76 student respondents who have taken Sharia Accounting courses. The software used is SPSS version 27 to process research data. Data analysis also includes descriptive statistical tests, classical assumption tests, and hypothesis testing. The results of data analysis show that Religious Background and Academic Value have a significant positive effect on Understanding Sharia Accounting Courses